In Situ Growth of Transition Metal Nanoparticles on Aluminosilicate Minerals for Oxygen Evolution. Issue 8 (6th May 2021) - Mei, Jun; Bai, Juan; Ayoko, Godwin A.; Peng, Hong; Liao, Ting; Sun, Ziqi
Abstract : Earth‐abundant and environmentally friendly aluminosilicate minerals can be one of the promising alternatives to develop cost‐effective energy conversion and storage devices. Herein, in situ growth of transition metal nanoparticles is proposed to modify two commonly available feldspar minerals, albite and microcline, for promoting electrocatalytic oxygen evolution reaction activity via a one‐step thermal reduction strategy. Three types of transition metal nanoparticles, namely, Ni, Co, and Fe, are selected to modify the albite or microcline surfaces. As expected, these modified products deliver enhanced catalytic activities compared to the pristine minerals. Particularly, Co‐modified microcline (C‐KASO) demonstrates the best performance that even outperforms the commercial RuO2 catalyst. This design by coupling low‐cost aluminosilicate minerals with active transition metal nanoparticles offers a new insight into directly utilizing the natural abundant resources to address the current energy crisis. Abstract : Two commonly available feldspar minerals, albite and microcline, are modified by in situ growth of three types of transition metal nanoparticles, Ni, Co, and Fe, for promoting electrocatalytic oxygen evolution reaction via a one‐step thermal reduction strategy. It is evidenced that the Co‐modified microcline catalyst demonstrates the best performance outperforming the commercial RuO2 catalyst.